Innovation to support wildfire risk-based decision-making: examining the incident strategic alignment process - Buettner, William Cole, author; Aldworth, Tyler, author; Greiner, S. Michelle, author; Beeton, Tyler A., author; Schultz, Courtney A., author; Springer Open, publisher (Colorado State University. Libraries, 2025)
Background: In the face of increased complexity, the USDA Forest Service (Forest Service) is emphasizing the use of risk-based spatial analytics and expert coaching of fire managers through consistent processes and practices to inform safer, effective, and strategic decision-making during incident management. The Incident Strategic Alignment Process (ISAP) integrates collaborative dialogue with risk management assistance (RMA) and other spatial analytics to develop and deploy a consistent, science-based strategic planning model for incident management. An important challenge is understanding the impact of frameworks like the ISAP to track their efficacy over time and their impact on approaches to incident management. Using concepts from the implementation of innovation literature, we investigated the following questions: (1) What is the perceived value of the ISAP according to line officers and incident managers who have used it? and (2) What factors affected the adoption and use of the ISAP at different system levels (i.e., individual, organizational, and cultural)? We examined three case studies: the 2023 Elkhorn Fire (Case 1), San Juan fires (Quartz Ridge, Bear Creek, Mosca fires; Case 2), and the Six Rivers Forest Lightning (SRF) Complex (Case 3), utilizing participant observation and 30 semi-structured interviews with key informants. Results: We found that interviewees valued the ISAP because it helped provide a consistent approach when communicating risk and strategy, fit into existing workflows, and facilitated difficult but necessary conversations. Challenges included a lack of knowledge and technical skills to support use, communication between incident managers and administrators, and unit dynamics and culture that impeded the adoption of new approaches. Facilitating factors included clear leadership communication and buy-in, favorable biophysical conditions for considering different management approaches, collaborative history, and the capacity to support the ISAP implementation. Conclusion: Our findings revealed organizational factors that influenced the use and application of wildfire innovation. Across cases, there was a wide understanding of the application of the ISAP. In line with interviewee recommendations, we suggest that additional education will be needed to help increase knowledge and communication in the context of new federal expectations. Finally, we found that the ISAP helped facilitate multiparty risk communication, which will be invaluable during high-emergency wildfires and criticism of organizational legitimacy.
Keywords: incident strategic alignment process; ISAP; risk-based decision-making; communication; alignment; fire management; innovation; organizational change